Quality of life in people with vitiligo: a systematic review and meta-analysis - Morrison, B.; Burden-Teh, Esther; Batchelor, Jonathan M.; Mead, E.; Grindlay, Douglas; Ratib, Sonia (Wiley, 2018)
Vitiligo is cosmetically disfiguring and has profound psychosocial effects due to stigmatization, problems in sexual function, anxiety, self-esteem and difficulty finding employment. Previous studies suggest a reduction in quality of life (QoL) due to vitiligo, but to date no systematic review has quantified this in comparison to people without vitiligo. Therefore, the aim of this review was to compare QoL in people with and without vitiligo.